1997
DOI: 10.1097/00000542-199704000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Analysis Measures Sedation and Memory Effects of Propofol, Midazolam, Isoflurane, and Alfentanil in Healthy Volunteers 

Abstract: The BIS both correlated well with the level of responsiveness and provided an excellent prediction of the loss of consciousness. These results imply that BIS may be a valuable monitor of the level of sedation and loss of consciousness for propofol, midazolam, and isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
465
2
25

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,140 publications
(520 citation statements)
references
References 24 publications
20
465
2
25
Order By: Relevance
“…Dogs and other species can also be quantified by bispectral monitoring (Greene et al 2003;Martin-Cancho et al 2003). In humans, BIS values above 90 indicate consciousness and values below 50 are considered to be ideal for surgical procedures (Glass et al 1997). The values described in this study demonstrate that BIS values above 95 for dogs do not differ from those in humans, since the animals were conscious and responsive to stimuli even after sedation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Dogs and other species can also be quantified by bispectral monitoring (Greene et al 2003;Martin-Cancho et al 2003). In humans, BIS values above 90 indicate consciousness and values below 50 are considered to be ideal for surgical procedures (Glass et al 1997). The values described in this study demonstrate that BIS values above 95 for dogs do not differ from those in humans, since the animals were conscious and responsive to stimuli even after sedation.…”
Section: Discussionmentioning
confidence: 60%
“…It is well known that co-administration reduces the dose of hypnotic required and minimises the adverse effects of each individual drug. Alfentanil can reduce the hypnotic and anaesthetic dose of propofol required in humans (Short et al 1992;Vuyk et al 1996;Glass et al 1997). The same dosage of propofol was used in each group, but a combination of propofol with a high dose of alfentanil resulted in lower BIS values (Group 2), while the administration of alfentanil alone does not change BIS values (Lysakowski et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Auditory evoked potential and oxygen consumption index (V . O 2 I) are the procedures for the objective evaluation of the depth of sedation 3,5 The bispectral index (BIS), has been used to evaluate the anesthetic depth, and the usefulness in the operating room has been established [6][7][8][9][10] . The usefulness of BIS in ICU to evaluate sedation depth is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…A bispectral index, Bis and many other variables are calculated by the Bis-monitor, and it is possible to obtain numerical information about these variables during anaesthesia with a very short delay. Bis has been found useful in monitoring anaesthetic depth [2,3], and several authors have reported that the method is promising in clinical practice [2,4,5]. The Bis-monitor can guide the anaesthetist during anaesthesia to obtain sufficient anaesthesia with reduced amounts of anaesthetic and allow a faster recovery from anaesthesia [4,5].…”
mentioning
confidence: 99%
“…The Bis-monitor can guide the anaesthetist during anaesthesia to obtain sufficient anaesthesia with reduced amounts of anaesthetic and allow a faster recovery from anaesthesia [4,5]. It has been shown that Bis depends on the anaesthetic agents given [3] and the position of the monitoring electrodes [6].…”
mentioning
confidence: 99%